Pemberdayaan Kelompok Tani dalam Perspektif Pembangunan Berpusat pada Rakyat di Desa Tri Sinar, Marga Tiga, Lampung Timur - Feni Rosalia; Aman Dwijono; Budi Harjo (Wacana Publik, 2022)
Farmer groups in Tri Sinar Village must be empowered so that farmers who join can improve their abilities so that they can be productive and generate maximum income. The village government is obliged to foster farmer groups so that they can function as organizations that can assist farmers in increasing their income. The purpose of the research is to find out the empowerment of farmer groups in the perspective of people-centered development, namely the people as subjects of development and have the freedom and active participation to take part in determining steps and strategies so that the goals of the farmer group can be achieved. The research type is descriptive qualitative with informants coming from farmer group members and Tri Sinar Village Government officials. Data collection using interviews to obtain data on the existence, activities and empowerment, while observation is used to confirm and ensure how empowerment to farmer groups so far. The results showed that the empowerment of farmer groups in Tri Sinar Village, Marga Tiga District, East Lampung Regency has been running but has not been centered on the people (farmers). this is because empowerment is more top-down, the system of providing assistance including the form/type of assistance is still an old pattern and routine in which assistance is still limited to seeds, fertilizers and pest medicines. Whereas the main need of farmers today is how through their farmer groups they can produce abundant agricultural products, with extensive marketing, packaging techniques that attract the market to the use of information technology in marketing